Archeologiczny przyczynek do problematyki tzw. krzyży pokutnych - Lechowicz, Zbigniew (Acta Universitatis Lodziensis. Folia Archaeologica, 1983)
In 1977 there were performed the salvage excavation researches near two stone penitential crosses at Żerniki. They resulted in determining the chronology of the crosses dating It back to 13th and 14th centuries. Between the se crosses there was discovered a single skeleton burial, which the author connects with a victim in the memory of which both stones were erected. Moreover in the vicinity of the crosses there were revealed fragmentarily preserved child burials dated to 17th century. The crosses from Żerniki represent an isolated find since they are situated outside a compact range of appearance of such relics, which in Poland encompasses only the Lower Silesia.